2019
DOI: 10.1038/s41385-019-0205-x
|View full text |Cite
|
Sign up to set email alerts
|

Colitis susceptibility in mice with reactive oxygen species deficiency is mediated by mucus barrier and immune defense defects

Abstract: Reactive oxygen species (ROS) generated by NADPH oxidases (NOX/DUOX) provide antimicrobial defense, redox signaling, and gut barrier maintenance. Inactivating NOX variants are associated with comorbid intestinal inflammation in chronic granulomatous disease (CGD; NOX2) and pediatric inflammatory bowel disease (IBD; NOX1); however Nox-deficient mice do not reflect human disease susceptibility. Here we assessed if a hypomorphic patient-relevant CGD mutation will increase the risk for intestinal inflammation in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…Loss of NOX1 expression has been shown to modulate the intestinal microbiota composition and to enhance overall bacterial growth [53]. Thus, H 2 O 2 generated by NADPH oxidases provides antimicrobial defense and, vice versa , loss-of-function mutations in NOX1 result in mucus layer disruption with bacterial penetration into crypts and subsequent intestinal inflammation [54]. Besides this, we have previously shown that another important mediator of mucus composition, the calcium-activated chloride channel regulator 1 (CLCA1), was decreased in GPx2 KO mice irrespective of the selenium status and associated shifts in GPx1 expression [55].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of NOX1 expression has been shown to modulate the intestinal microbiota composition and to enhance overall bacterial growth [53]. Thus, H 2 O 2 generated by NADPH oxidases provides antimicrobial defense and, vice versa , loss-of-function mutations in NOX1 result in mucus layer disruption with bacterial penetration into crypts and subsequent intestinal inflammation [54]. Besides this, we have previously shown that another important mediator of mucus composition, the calcium-activated chloride channel regulator 1 (CLCA1), was decreased in GPx2 KO mice irrespective of the selenium status and associated shifts in GPx1 expression [55].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Nox4 levels remained elevated in intestinal inflammation without any significant increase during development and progression of fibrosis in this CD-like animal model. In wildtype C57BL/6J mice we reported elevated Nox4 expression in acute chemical colitis [ 29 ] and observed a spike of Nox4 levels at the onset of infectious colitis (not shown). We conclude that expression of NOX4 is consistently elevated in human and murine colitis, during fibrogenesis and in strictures.…”
Section: Resultsmentioning
confidence: 97%
“…Using combinations of various Nox isoform inactivation and knockout mouse strains we observed that maintaining catalytically active Nox4 delayed the mortality rate of dextran sodium sulfate (DSS) treated, Nox1-3 inactivated mice [ 29 ]. To study this protective phenotype in more detail wildtype mice and Nox4 −/− mice were exposed to DSS for 6 days, which resulted in accelerated body weight loss and increased disease severity in Nox4-deficient mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…and ultimately causes cellular dysfunction [ 24 , 35 , 36 ]. In addition, the deficiency of ROS accompanies malfunctions in the immune system, which elevate the danger of bacterial spreading and trigger autoimmune disorder [ 37 , 38 ]. In this regard, the regulation of endogenous antioxidant enzymes including SOD1 and SOD2 plays essential roles in controlling redox homeostasis via well control between ROS generation and ROS scavenging [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%